Denaturing gradient gel electrophoresis used to monitor the enrichment culture of aerobic chemoorganotrophic bacteria from a hot spring cyanobacterial mat. - Santegoeds, C M (1996)
Previous studies investigating microbial diversity in the Octopus Spring cyanobacterial mat community (Yellowstone National Park) have shown a discrepancy between bacterial populations observed by molecular retrieval and cultivation techniques. To investigate how selective enrichment culture techniques affect species composition, we used denaturing gradient gel electrophoresis (DGGE) separation of PCR-amplified 16S rRNA gene fragments to monitor the populations contained within enrichment cultures of aerobic chemoorganotrophic bacteria from the ca. 50 degrees C region of the mat community. By varying the degree of dilution of the inoculum, medium composition, and enrichment conditions and duration and by analyzing the cultures by DGGE, we detected 14 unique 16S rRNA sequence types. These corresponded to alpha-, beta-, gamma-, and delta-proteobacteria, Thermus relatives, and gram-positive bacteria with high G + C ratio and, at the highest inoculum dilutions, Chloroflexus aurantiacus relatives, which were estimated to still be approximately 300 times less abundant than cells of the mat primary producer, Synechococcus spp. Only three of these populations were previously cultivated on solidified medium after similar enrichment. Only two of these population have 16S rRNA sequences which were previously cloned directly from the mat. These results reveal a diversity of bacterial populations in enrichment culture which were not detected by either molecular retrieval or strain purification techniques.